Sequential enlarging Lu2O3:Eu phosphor mono-spheres into near micro-meter size range by controlled nucleation and growth for attaining optimum photoluminescence properties. Issue 19 (1st October 2022) - Ma, Chang; Li, Xiaodong; Zhang, Mu; Zhu, Qi; Sun, Xudong
Abstract: Uniform phosphor mono-spheres have received continuously increasing attention owing to their excellent luminescence properties. Submicron/near micron-sized Lu2 O3 :Eu mono-spheres were successfully prepared by a facile and modified homogeneous precipitation technique from corresponding single-source precursor of Lu(OH)CO3 :Eu⋅ n H2 O, without the assistance of any dispersants. The sizes of the precursor spheres can be tuned in the range of 56–790 nm via controlling the primary particle nucleation and particle growth in the homogeneous precipitation. After calcination at 1000 °C, the synthesized precursor spheres (165–790 nm) were converted to Lu2 O3 :Eu (110–630 nm) without changing their original spherical shape and excellent dispersion. The particle size-dependent photoluminescence properties of Lu2 O3 :Eu mono-spheres were investigated in detail. Enhanced photoluminescence intensity, shorter lifetime, higher external quantum efficiency and almost the same CIE chromaticity coordinates were observed for a particle size of 480 nm. Moreover, temperature-dependent photoluminescence spectra indicated the obtained phosphor mono-spheres have good thermal stability.